2019
DOI: 10.1002/er.5050
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum‐ and vanadium‐containing perovskite electrocatalysts for dissociation of H 2 S

Abstract: Summary Catalytic operations, achieving considerable energy savings, continue getting wider application especially in clean energy systems. Perovskite materials, owing to their chemical and thermal stability, can be conveniently used as catalysts and electrode materials at wide temperature ranges. Hydrogen sulfide (H2S) offers a new and abundant source of hydrogen, the ultimate energy carrier. In the present work, change in electrical conductivity of catalysts obtained by adding molybdenum (Mo) and vanadium (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
3
0
2
Order By: Relevance
“…Karaismailoglu et al reported the thermal decomposition of H 2 S over perovskite materials for the first time . The LaSr 0.5 V 0.5 O 3 , LaSr 0.5 Mo 0.5 O 3 , and LaMoO 3 showed 37.7%, 36%, and 34.7% conversions of H 2 S at 950 °C, respectively.…”
Section: Catalytic Splitting Of H2smentioning
confidence: 99%
“…Karaismailoglu et al reported the thermal decomposition of H 2 S over perovskite materials for the first time . The LaSr 0.5 V 0.5 O 3 , LaSr 0.5 Mo 0.5 O 3 , and LaMoO 3 showed 37.7%, 36%, and 34.7% conversions of H 2 S at 950 °C, respectively.…”
Section: Catalytic Splitting Of H2smentioning
confidence: 99%
“…Aynı Nazif Hocamızın, bir sebeple üzülmesine neden olduğu araştırma görevlisinin kapısına kadar gittiği ve "Ben seni kapıdan kovsam, sen pencereden içeri gireceksin" diyerek muhatabının sıkıntılı durumunu gidermek için çaba içerisinde oluşunu da ders alınması gereken bir başka husus olarak aktaralım. 23 Nazif Hocanın kendilerinden ders aldığı Ahmet Ateş ve Nihat Çetin Hocalarla ilgili öğrencilerine zaman zaman aktardığı bir anekdot da öğreticidir. Bu hocalarımız fakülteye bir asistan almak istediklerinde, katılımcılara bir sayfa yazılı metin verir ve bunun bir kopyasını yazıp getirmelerini isterlermiş.…”
Section: ġLmî Disiplin Dakiklik Okuma Aģkı Ve Yazmaunclassified
“…diye sorarmış." 28 Nazif Şahinoğlu'nun öğrencilerine verdiği değerin bir ifadesini de Veyis Değirmençay'ın kaleminden okuyalım: "Kitabının müsveddesini bendenize okutması da benim için ayrıca bir gurur kaynağıdır; çünkü söz konusu eseri baştan sona okuyup bazı yerlerde gözden kaçan hususları hocama arz etmiş ve hocamın iltifatlarına mazhar olmuştum." 29 Kitapta ayrıca Nazif Şahinoğlu Hocanın doktora ve yüksek lisansta danışmanlık yaptığı kişilere ilişkin bir listenin verilmiş olması hatırlatılması gereken hususlardan biridir.…”
Section: ġLmî Disiplin Dakiklik Okuma Aģkı Ve Yazmaunclassified
“…However, the direct decomposition of H 2 S is a highly endothermic process (with a reaction enthalpy of +169.4 kJ/mol) with limited thermodynamic conversion at temperatures below 1000 K . Aside from thermocatalytic efforts for direct H 2 S decomposition, , there have been attempts to achieve faster kinetic rates at milder temperatures using electrocatalytic, , photocatalytic, plasma-induced, and microwave-assisted approaches. , Chemical looping , has also been implemented to circumvent the thermodynamic limitation of this reaction. While these studies represent valuable progress toward the direct decomposition of H 2 S at milder temperatures, difficulties with scale-up due to the energy source or the catalyst are still major challenges.…”
mentioning
confidence: 99%
“…The produced H 2 can also be fed back into the hydrodesulfurization reaction, forming a closed loop and mitigating the need for an external H 2 supply (which, in current industrial practice, typically originates from a CO 2 -emitting source). However, the direct decomposition of H 2 S is a highly endothermic process (with a reaction enthalpy of +169.4 kJ/mol) 8 with limited thermodynamic conversion at temperatures below 1000 K. 6 Aside from thermocatalytic efforts for direct H 2 S decomposition, 9,10 there have been attempts to achieve faster kinetic rates at milder temperatures using electrocatalytic, 11,12 photocatalytic, 13−19 plasma-induced, 20 and microwave-assisted approaches. 21,22 Chemical looping 23,24 has also been implemented to circumvent the thermodynamic limitation of this reaction.…”
mentioning
confidence: 99%